IMPLEMENTASI PENGINTEGRASIAN KEISLAMAN DALAM PENGENALAN KONSEP MATEMATIKA ANAK USIA DINI - Sabri, Ahmad; Warmansyah, Jhoni; Amalina, Amalina; Aswirna, Prima (Math Educa Journal, 2020)
The purpose of this study is to describe the implementation of Islamic integration in introducing mathematical concepts in early childhood. This research uses descriptive qualitative. Subjects were Assakinah's Integrated Islamic Kindergarten B children and the informants in this study were teachers and school principals. Data validity techniques in this study used triangulation and used reference materials. The results of research on the implementation of Islamic integration in the introduction of mathematical concepts to children B Integrated Islamic Kindergarten is to get children to read basmalah before starting the process of training mathematics learning and acquiring with hamdalah, introducing study programs using Hijri guidelines, introducing children to children - the story of mathematical figures in Islamic civilization, introducing Islamic ornaments in the concept of geometry, introducing associations through the use of Islamic terms and names, and using the method of playing in algebra.